2003
DOI: 10.1074/jbc.m303868200
|View full text |Cite
|
Sign up to set email alerts
|

Two Distinct Gb3/CD77 Signaling Pathways Leading to Apoptosis Are Triggered by Anti-Gb3/CD77 mAb and Verotoxin-1

Abstract: Globotriasosylceramide (Gb3), a neutral glycosphingolipid, is the B-cell differentiation antigen CD77 and acts as the receptor for most Shiga toxins, including verotoxin-1 (VT-1). We have shown that both anti-Gb3/ CD77 mAb and VT-1 induce apoptosis in Burkitt's lymphoma cells. We compared the apoptotic pathways induced by these two molecules by selecting cell lines sensitive to only one of these inducers or to both. In all these cell lines (including the apoptosis-resistant line), VT-1 was transported to the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
77
1

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(80 citation statements)
references
References 47 publications
1
77
1
Order By: Relevance
“…In our present study, we used only the nontoxic STxB. It has been shown by several studies that STxB is capable of apoptosis induction in Burkitt's lymphoma cells, although it is not able to inhibit protein synthesis (33,36,38).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our present study, we used only the nontoxic STxB. It has been shown by several studies that STxB is capable of apoptosis induction in Burkitt's lymphoma cells, although it is not able to inhibit protein synthesis (33,36,38).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies showed that human intestinal epithelium (11,15) and purified epithelial cells (12,33,34) were Gb 3 -negative. In agreement with these studies, we found that normal human colonocytes were not labeled by STxB, and in our previous in vivo experiments on mice, STxB did not accumulate in these cells (30).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, it has been known that holotoxin initial internalization will be A subunit-independent, and two pathways have been identified as applicable to holotoxin endocytosis (Khine et al 2004). Moreover, two distinct Gb3/ CD77 signaling pathways leading to apoptosis have been triggered by Anti-Gb3/CD77 mAb and Stx (Tétaud et al 2003). Therefore, different intracellular routing may play a pivotal role in cell susceptibility and triggering a different pathway for apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…In some cell types the Shiga toxins, as a long term effect, induce expression and secretion of pro-inflammatory cytokines, including TNF-, IL-1, IL-6 and IL-8 [6,11,12]. Interestingly, the secreted cytokines can induce synthesis of Gb3 in other cell types, thereby sensitizing these cells to the toxin [13].…”
Section: Introductionmentioning
confidence: 99%